Optimal planning and operation of combined cooling heat and power systems in future energy networks - Ren, Xuejing (2018)
Nowadays, energy crisis has become a serious problem that many countries are facing with. In electric power industry, clean energy generation is considered as a method that are more efficient and environmental friendly. The close relation between power, cooling and heat make the combination of these energies in a system become possible. In this final year project, an optimal planning and operation dispatch of the micro-grid with combined cooling, heat and power (CCHP) system was proposed. The system presented in this project comprised multi-energy system and energy conversion devices. The objective function was the minimum of net present cost. In this optimization problem, mixed-integer linear programming and software YALMIP were adopted to search for the best solution. The solving method was applied to both separation generation and CCHP system as cases study. The results of simulation demonstrated that the proposed micro-grid with CCHP can decrease the consumption of fuel and increase the net present value of whole system. The study of this project proved the advantages of micro-system with CCHP system, and it deserves further research and can be widely used to alleviate energy crisis.